Niger : Poverty Reduction Strategy Paper; 2004 and 2005 Annual Progress Reports; Joint Staff Advisory Note. (IMF Staff Country Reports; Country Report ;, 2007)
This Joint Staff Advisory Note focuses on the Poverty Reduction Strategy Paper (PRSP) 2004 and 2005 Annual Progress Reports for Niger. Overall, progress in the implementation of the PRSP in 2004 and 2005 was broadly positive, given the challenges posed by a drought and locust plague in the second half of 2004 and a severe food crisis in the second and third quarters of 2005. A Core Welfare Indicators Questionnaire completed in 2005 indicated that the poverty level was at 62.1 percent.